Punching shear of flat slabs with openings, moment transfer and shear reinforcement - Santos, Júlia Borges dos (2023)
Tese (doutorado) — Universidade de Brasília, Programa de Pós-Graduação em Estruturas e Construção Civil, Faculdade de Tecnologia, 2023.